Quantitative Analysis of the Interactive Influence for Harmonic Emission in Wind Farms - Shi, Jinhui; Chen, Wei; Wei, Zhanhong; Pei, Xiping; Sun, Xuebo (Frontiers in Energy Research, 2022)
In the process of large-scale wind farms integrated into the power system, the harmonics interaction among wind farms causes potential threats to the safe and stable operation of the power grid. In order to effectively control the harmonics of the wind power grid-connected system, quantitative analysis of harmonic interaction is very necessary and significant. Therefore, this paper firstly explains the harmonic interaction among wind farms from the perspective of the primary and secondary emission. Secondly, we use the concept of harmonic impedance to analyze the mechanism of harmonic interaction, and put forward a calculation method for quantitative analysis of harmonic interaction. Thirdly, the influence resulted from the wind farm self-impedance, the transfer impedance and Static Var Generator to the harmonic interaction are quantitatively analyzed by the calculation method. Finally, taking multiple wind farms in actual operation as a case, the effectiveness of the method is verified by time domain simulation.